A STUDY ON FINANCIAL LITERACY AMONG YOUNGSTERS IN CHENNAI CITY - Ambuli, Dr. T.V. (The journal of contemporary issues in business and government, 2022)
Financial literacy is a combination of skill, knowledge and attitude towards financial related aspects of an individual. It provides to take proper financial decision for the person who need of it. Research has been organized throughout the world in order to identify and measure the financial literacy level .The government has been conducted a financial literacy survey in our country. In general most of the survey insist to find the level of financial literacy. This article focuses to identify the level of financial literacy of the youngster in Chennai and it identifies the Excellency with respect to financial decision. This study identifies that income, qualification, gender and age affects the level of financial literacy. It also finds out the financial alternatives preferred by youngsters. With the help of this study required strategies can be identified and for the betterment in financial decision by the youngster in Chennai city.